The Holocaust : theoretical readings - Levi, Neil; Rothberg, Michael (Edinburgh University Press, 2003)
This anthology addresses the relationship between the events of the Nazi genocide and the intellectual concerns of contemporary literary and cultural theory in one volume. It collects together both classic and new theoretical writings.